Effects of Xiaoshuan enteric-coated capsule on neurovascular functions assessed by quantitative multiparametric MRI in a rat model of permanent cerebral ischemia. Issue 1 (December 2016) - Zhang, Jian; Zou, Haiyan; Zhang, Qiuxia; Wang, Lei; Lei, Jianfeng; Wang, Yali; Ouyang, Junyao; Zhang, Yi; Zhao, Hui
Abstract Background Buyang Huanwu Decoction (BYHWD) is a Traditional Chinese Medicine (TCM) formula for treating stroke-induced disability.Xiaoshuan enteric-coated capsule (XSECC), derived from the formula BYHWD, is a drug approved by the China Food and Drug Administration (CFDA) for stroke management. To further investigate the potential protective effects of XSECC on neurovascular functions, we endeavour to monitor the neurovascular functions using multimodal magnetic resonance imaging (MRI) and evaluated histopathological changes of neurovascular unit (NVU) after stroke. Methods Ischemic stroke was induced by permanent middle cerebral artery occlusion (pMCAO). XSECC (420 mg/kg) was orally administered 2 h after stroke and daily thereafter. T2-weighted imaging (T2WI), T2 relaxometry mapping and diffusion tensor imaging (DTI) were used to measure cerebral infarct volume, edema and white matter fiber integrity, respectively. Neurochemical metabolite levels were monitored by1 H-magnetic resonance spectroscopy (1 H-MRS). Arterial spin labeling (ASL) – cerebral blood flow (CBF) measurements and structural magnetic resonance angiography (MRA) images provided real-time and dynamic information about vascular hemodynamic dysfunction on the 3rd, 7th and 14th days after pMCAO. At the last imaging time point, immunohistochemistry, immunofluorescence as well as transmission electron microscopy (TEM) were used to test the microscopic and ultrastructural changes of NVU. Results T2WI, T2 relaxometry mapping and Fractional anisotropy (FA) in DTI showed that XSECC significantly reduced cerebral infarct volume, relieved edema and alleviated nerve fiber injuries, respectively.1 H-MRS provided information about improvement of neuronal/glial metabolism after XSECC treatment. Moreover, ASL – CBF measurements combined with MRA showed that XSECC significantly increased CBF and vascular signal strength and alleviated ischemia-induced morphological changes of arteries in ischemic hemisphere within 14 days after stroke. In addition, neuron specific nuclear protein (NeuN), glial fibrillary acidic protein (GFAP), CD34 staining and TEM detection indicated that XSECC not only ameliorated neuronal injury, but also reduced endothelial damage and inhibited astrocyte proliferation. Conclusions Our results suggested that XSECC has multi-target neurovascular protective effects on ischemic stroke, which may be closely correlated with the improvement of cerebral blood supply and neuronal/glial metabolism.